Bilingual Terminology Extraction based on Translation Patterns - Simões, Alberto (2009)
Parallel corpora are rich sources of translation resources. This document presents a methodology for the extraction of bilingual nominals (terminology candidates) from parallel corpora, using translation patterns. The patterns proposed in this work specify the order changes that occur during translation and that are intrinsic to the involved languages syntaxes. These patterns are described in a domain specific language named PDL (Pattern Description Language), and are extremely efficient for the detection of nominal phrases.